DUXAP8 a Pan-Cancer Prognostic Marker Involved in the Molecular Regulatory Mechanism in Hepatocellular Carcinoma: A Comprehensive Study Based on Data Mining, Bioinformatics, and in vitro Validation - Yue, Chaosen (Onco Targets Ther, 2019)
BACKGROUND: Double homeobox A pseudogene 8 (DUXAP8) has been identified as a key regulator at the posttranscriptional level in various types of cancers. However, whether DUXAP8 has a role in hepatocellular carcinoma (HCC) progression remains to be determined. Here, we aimed to investigate the potential clinical value of DUXAP8 as a pan-cancer marker, and its role in HCC development through an integrated analysis strategy and in vitro experimental validation. METHODS: Comprehensive analysis was performed using data mined from public databases to evaluate the expression patterns and clinical value of DUXAP8 in human pan-cancers. Bioinformatics analysis was performed to investigate the potential biological functions of DUXAP8 in HCC based on TCGA database. Real-time qPCR analysis was used to examine the expression levels of DUXAP8 in HCC tissue samples and cell lines. DUXAP8-siRNA was used to silence DUXAP8 in the Hep-G2 cell line to examine the role of DUXAP8 in HCC cell proliferation and invasion. RESULTS: DUXAP8 was significantly upregulated in various types of human cancers and could serve as a potential pan-cancer diagnostic and prognostic biomarker. Bioinformatics analysis suggested that DUXAP8 might be involved in the regulation of the biological processes of HCC cell cycle, cell division and cell proliferation. Additionally, downregulation of DUXAP8 inhibited HCC cell proliferation and invasion in vitro. CONCLUSION: This study revealed that DUXAP8 may serve as a potential pan-cancer prognostic and diagnostic marker in humans. In addition, DUXAP8 promoted HCC cell proliferation and invasion, suggesting that it may represent a novel therapeutic target for HCC.